Contribution to research after foundations for defining the conception of machining system modular design - Rekecki, Jožef; Zeljković, Milan; Borojev, Ljubomir; Gatalo, Ratko; Hodolič, Janko (Journal of Production Engineering, 1989)
The paper presents some results of research into the geometric and technological characteristics in the late construction of turning machines, grinders, drilling machines, and machining centers. This research forms the foundation for designing their primary characteristics and defining the concept of modular design. Despite this, the initial approach was that one of the most efficient methods for forecasting the technical characteristics of machining systems is trend extrapolation.